Follower Mindfulness and Well-Being: The Mediating Role of Perceived Authentic Leadership and the Moderating Role of Leader Mindfulness - Zhang, Jing; Song, Lynda J.; Ni, Dan; Zheng, Xiaoming (Frontiers in Psychology, 2020)
Drawing on implicit leadership theory and the mindfulness literature, we propose that perceived authentic leadership mediates the relationship between follower mindfulness and follower well-being. Leader mindfulness plays a moderating role in this process. We validated these hypotheses with the two-wave data from 56 leaders and 275 followers in two private enterprises located in China. We used Mplus 8.0 to test our hypotheses. Consistent with our hypotheses, the results showed that perceived authentic leadership mediated the positive relationship between follower mindfulness and follower well-being. Higher leader mindfulness enhanced the effect of follower mindfulness on perceived authentic leadership, and also strengthened the indirect effect of follower mindfulness on follower well-being via perceived authentic leadership. The theoretical and managerial implications are further discussed in the light of these findings.